Studies on Desorption Behaviuor of Garlic (Allium sativum Linn.) Slices - Dhingra, Devinder; Paul, Shashi (Journal of Agricultural Engineering, 2004)
Moisture desorption properties of garlic (Allium sativum cv. G282) were investigated at 40, 50 and 60degree C temperature and relative humidity's ranging from 11% to 82% using the gravitmetric static method. The garlic slices Were allowed to equilibrate in constant humidity environment maintained by salt solutions. Tbe effect of temperature and equilibrium relative humiditY, on the equilibrium moisture content was highly siginificant (P&lt0.0001). Four models namely Chung-Pfost, modified Henderson, modifted Halsey and modified exponential were evaluated (the correlation coefficient and sum of squares of residuals, SSR) to determine the best fit for the experimental data. The modified Henderson, modified Halsey and modified exponential models were found adequate and mathematically similar. The modified exponential model was found superior for characterizing the desorption behaviour of garlic slices in the temperature and relative humidity range investigated.